Training and learning in Mario Osorio Marques (Revista Contexto & Educação, 2025)
The article focuses on the trajectory of Professor Mario Osorio Marques, highlighting his extensive research contributions to education through his main book publications. Each publication is contextualized within the theoretical framework it belongs to, the perspectives that support it, and the innovative aspects it presents. The second part of the article addresses a theme to which the author has made a significant contribution through his extensive research: human learning, including its implications for formal teaching processes. In conclusion, the article emphasizes the life legacy of Professor Mario Osorio Marques, with reflections affirming that the theoretical perspectives underpinning his vast body of research are practically effective, as attested by those who knew and worked with him.
Keywords: Mario Osorio Marques; Education research; Human formation; Learning